2014
DOI: 10.5515/kjkiees.2014.25.12.1201
|View full text |Cite
|
Sign up to set email alerts
|

Aperture Cut-off Filter for Reduction of Electromagnetic Field Penetration through a Slot in Conducting Screens

Abstract: The purpose of this paper is to present the aperture cut-off filter for reduction of electromagnetic field penetration through a slot in conducting screen. The reduction characteristics of electric field penetration by the aperture cut-off filter are considered. In order to establish the concept of the aperture cut-off filter, the integral equation on the slot aperture field distribution is derived and solved by method of moments, and the reduction characteristics of penetration electric fields for the inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…These results are similar to the single plate case and operate as an aperture cutoff filter. For the single plate, the penetrated electric field is reduced to zero by the two parallel wire lengths of around 0.27λ [12,16]. Fig.…”
Section: Numerical Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These results are similar to the single plate case and operate as an aperture cutoff filter. For the single plate, the penetrated electric field is reduced to zero by the two parallel wire lengths of around 0.27λ [12,16]. Fig.…”
Section: Numerical Results and Discussionmentioning
confidence: 94%
“…Recent studies have focused on the reduction of electromagnetic penetration through narrow slots in a conducting screen, and electric shielding effectiveness has been considered for a dual plate with narrow slots [12][13][14][15][16][17][18]. The resonant behavior of a small aperture backed by a conducting body has been reported [19], and enhanced resonance transmission has been investigated on shaped apertures, narrow small slots, and small square slots using two parallel wires (acting as a reactance) loaded in the slot [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In areas with electromagnetic pulses, the protection of electronic equipment and buildings is also of considerable interest for achieving high shielding effectiveness (SE). Recently, some studies have reported the reduction of electromagnetic penetration through narrow slots in a single-layer shielding structure by connecting parallel wires to the slot [8][9][10][11]. This structure involves wires connected to the slot acts as an aperture-cutoff filter (ACF), as explained in a previous article [11].…”
Section: Introductionmentioning
confidence: 99%
“…The penetration of electromagnetic fields and wave transmission through a slot aperture in a conducting screen have been extensively studied [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16]. The reduction problem of the electromagnetic field penetration through a half-wavelength narrow slot has been investigated in the electromagnetic compatibility (EMC) fields as an aperture cutoff filter [17,18]. A very small number of electromagnetic waves are transmitted through small slots.…”
Section: Introductionmentioning
confidence: 99%